Dampak Pandemi Covid-19 Terhadap Pendapatan Petani Di Aceh Barat - Munakahad, Delfa; Rosmanidar, Rosmanidar; Amraida, Lusy; Lizikkrina, Reza (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
In early 2020, the world was taken by surprise with the outbreak of the COVID-19 pandemic, which caused a major reduction in public income, including within the agricultural sector. This research investigates the effects of the pandemic on the agricultural sector in Aceh Barat, specifically examining the impact on tobacco farming production and the income of farmers. The study employs a descriptive quantitative approach, with 38 respondents chosen through a saturated sampling method. The results suggest that the success of tobacco farming is influenced by factors such as the size of land cultivated by farmers, with variations in land area affecting both productivity and income. Since the onset of the pandemic, tobacco farmers in Aceh Barat have experienced a drop in income of around 40% compared to pre-pandemic levels.